2023
DOI: 10.1021/acs.est.2c07253
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Simulating the Global Spatial Heterogeneity of Air Quality and Source Sector Contributions: Insights into the Global South

Abstract: High-resolution simulations are essential to resolve fine-scale air pollution patterns due to localized emissions, nonlinear chemical feedbacks, and complex meteorology. However, high-resolution global simulations of air quality remain rare, especially of the Global South. Here, we exploit recent developments to the GEOS-Chem model in its high-performance implementation to conduct 1-year simulations in 2015 at cubed-sphere C360 (∼25 km) and C48 (∼200 km) resolutions. We investigate the resolution dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Those uncertainties are expected to be reduced along with the improvement of chemistry mechanisms in the GEOS-Chem adjoint. Besides, the model horizontal resolution (≈25–30 km) may misrepresent emission impacts on air pollution to some extent as it could not fully capture the detailed pollution distributions and colocated air pollutant hotspots, especially for urban regions. Finally, the effect of the COVID-19 lockdown on short-term emission change was not quantified in this work. As presented in Figure S20, there was no steep reduction in emissions or sudden change in sectoral proportion in 2020, implying that air pollution controls dominated the reductions of anthropogenic emissions from a long-term perspective.…”
Section: Policy Implication and Uncertaintymentioning
confidence: 99%
“…Those uncertainties are expected to be reduced along with the improvement of chemistry mechanisms in the GEOS-Chem adjoint. Besides, the model horizontal resolution (≈25–30 km) may misrepresent emission impacts on air pollution to some extent as it could not fully capture the detailed pollution distributions and colocated air pollutant hotspots, especially for urban regions. Finally, the effect of the COVID-19 lockdown on short-term emission change was not quantified in this work. As presented in Figure S20, there was no steep reduction in emissions or sudden change in sectoral proportion in 2020, implying that air pollution controls dominated the reductions of anthropogenic emissions from a long-term perspective.…”
Section: Policy Implication and Uncertaintymentioning
confidence: 99%
“…7−9 Recent advances in global fine-resolution CTMs have demonstrated better capability of resolving fine-scale air pollution patterns. 5,6,10,11 Nonetheless, the spatial heterogeneity of the simulated surface PM 2.5 to AOD relationship is complicated by the coupled effects of the spatial variation of PM 2.5 and of the covariation extent between the surface and total column aerosol abundance. The effects of model resolution on the accuracy of geophysical PM 2.5 inference are largely unknown and require further investigation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,16 Nonlinear chemical mechanisms further deteriorate an accurate representation of secondary aerosols at coarse resolution. 6,10,17 For example, a prior study found that enhanced mixing between oxidants and precursors at coarse resolution (∼200 km) leads to 18% more sulfate production over southeastern Europe than at fine resolution (∼25 km). 6 Spatial gradients of air pollution are especially better resolved at fine resolution over mountainous regions with strong local pollution and weak dispersion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations